Predictive musculoskeletal simulation for functional electrical stimulation cycling : from optimization to experimental validation in spinal cord injury - Peres, Alexandre Bernardi (2026)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, Programa de Pós-Graduação em Engenharia Elétrica, 2026.